Determine The Factors That Influence Profit Growth at Village Credit Institutions in Badung District - Agustina, Putu Ayu Anggya; Praningtyas, Elisabeth Ria Viana; Subekti, Rini (Universitas Batanghari Jambi, 2024)
Village Credit Institutions or VCIs, function similarly to banks. There are variations in performance measurement, though (health status). The VCIs employ the Bali Province Governor's operational regulations number. 44 of 2017, which accounts for this discrepancy. The VCIs of Bali Province's Badung Regency were one of the VCIs examined. Because Badung Regency VCIs have the highest assets when compared to other VCIs in Bali Province's districts and cities, the goal is to look at their profit growth. The likelihood that VCIs may fail owing to poor management and a lack of public transparency on their state of health does not disappear even with their substantial asset base. This study examines the effect of VCI health on profit growth empirically. The Capital, Asset, Management, Earnings, and Liquidity (CAMEL) examination on profit growth is part of this degree of soundness. Study observation period: 2016–2022. Using a quantitative research approach and secondary data from Empowerment Institutions of Village Credit Institutions (EIVCI) in the Badung Regency, the total population is 854 VCIs. A non-probability sampling strategy combined with a purposive sampling technique was used to determine the sample. This study's analysis method makes use of multiple linear regression. The study's findings indicate that operational expenses have a beneficial impact on profit growth when it comes to operating income, loan-to-deposit ratio, net profit margin, and return on assets. In the meantime, profit growth is negatively impacted by the caliber of producing assets. In the meanwhile, profit growth is unaffected by the capital adequacy ratio and current ratio. The research's practical application is to arm VCIs with knowledge so they can train VCI administrators to manage VCIs. In addition, the availability of profit growth analysis using CAMEL helps boost public trust in the use of VCIs.